IDENTIFICATION OF CATALASE-PRODUCING BACTERIA IN ECOENZYMES FROM FOOD WASTE USING GEN 16S rRNA - Alfi Syaifuddin; Andang Syaifudin; Asri Febriana (JURNAL PENA SAINS, 2026)
Food waste is a global problem that has a negative impact on the environment and society as a whole because it endangers food security and the sustainability of the food supply chain in the long term. One of the efforts made to overcome the problem of kitchen waste and food waste is by making ecoenzymes made from the fermentation of organic kitchen waste. Ecoenzymes are naturally produced through the fermentation of fruit and vegetable waste by anaerobic bacteria. Among the components of ecoenzymes is the enzyme catalase, which helps break down excess hydrogen peroxide. One source of catalase is microorganisms such as bacteria and fungi. In identifying bacteria in ecoenzymes, molecular testing using the 16S rRNA gene can be employed, as it can determine the specific type of bacteria. The objectives of this study are to determine the number of bacterial isolates producing catalase enzymes in ecoenzymes from food waste and to identify the bacterial species in ecoenzymes from food waste that produce catalase enzymes using the 16S rRNA DNA marker. This study employs an experimental research design with both qualitative and quantitative approaches. This study showed that there were three isolates (A, B, and C) that were positive for producing catalase enzymes. Based on molecular testing using the 16S rRNA gene, the three isolates were most closely related to the species B. subtilis. This study demonstrated the presence of catalase enzyme activity in ecoenzymes from food waste and the presence of B. subtilis bacteria, which play a role in disease control in plants.